Efeito do treinamento físico combinado com laser de baixa potência em monoartrite experimental - Silva, Marcelo de Paula Alves da (2014)
Monoarthritis (MA) is caused by single-joint inflammation and represents a considerable public health problem worldwide. To evaluate this pathology two protocols were used (P1 and P2). In P1, the effects of low level laser therapy (LLLT) in the influx of inflammatory cells, the release of inflammatory mediators, metalloproteinases (MMPs) and the process of intra-articular repair, were evaluated. In P2 the combination of exercise training (ET) and the LLLT were used to evaluate systemic changes using the heart rate variability (HRV) and local joint changes in experimental model of monoarthritis induced by zymosan. In both protocols male Wistar rats (220-280 g) was used. Rats received intra-articular injection of zymosan (1 mg / 50 mL of sterile saline) into the right knee. P1 rats were irradiated immediately, 1 hour and 2 hr after zymosan administration with LLLT (660 nm, 10 mW, 2,5 J / cm2, 10 s). In the positive control group, rats were injected with Dexamethasone (antiinflammatory agents) 1 hr before zymosan.administration. P2 rats were adapted to the treadmill (10 min / d 0.3 5 km / h) after 48 h the zymosan was administrated and the moderate ET and LLLT (660 nm, 5 mW, 2,5 J/cm2, 20s, 0.04 cm2, 0.1 w/cm2) was applied. The LLLT was applied twice a week, always before TF, during 4 weeks. Our results demonstrated that in P1 LLLT treatment significantly inhibited the influx of leukocytes, release of IL-1 and IL-6 and also metalloproteinase activity 2 to 9. In P2 the measurement of arterial pressure (AP) and heart rate variability (HRV) was measured. Trained rats had lower body weight, increased maximum speed racing and lower heart rate compared to the sedentary groups. Furthermore, ET rats showed an increase in pulse interval (PI) and decrease in the low frequency band (LF) and the systolic arterial pressure variance (VAR SAP) compared to sedentary group MA. ET associated with LLLT also showed a decrease in (LF) and Reason of Band High Frequency / Low Frequency (HF/LF), increase VAR SAP, variance RR (VAR-RR) e HF. compared to the sedentary group with MA. In addition, there was an improvement in functional capacity and a decrease of leukocyte influx in the joint cavity. Histological analysis showed a histoarchitecture preserved the synovial membrane and a reduction in collagen deposit in the groups with ET and ET associated and LLLT compared to the sedentary group with MA. ET and LLLT caused a reduction in the release of IL-1β in synovial fluid and synovial membrane. Furthermore, IL-10 was increased in the group association of ET and LLLT. LLLT was effective in reducing inflammation and inhibits activation of proteases (gelatinase), suggesting less degradation of collagen tissue in an experimental model. In MA occurs an imbalance of the sympathetic system, suggesting an early autonomic involvement. A moderate ET program associated with LLLT may have beneficial effects on the cardiovascular autonomic balance and improved functional capacity. With regard to deleterious effects in the rat knee, ET and LLLT association was effective in protecting the joint in an experimental model of monoarthritis, leading to an improvement in the regulation of inflammatory cytokines and better intra articular histoarchitecture organization.